One-incubation one-hour multiplex ELISA enabled by aqueous two-phase systems. Issue 10 (6th April 2020) - Tongdee, Mintra; Yamanishi, Cameron; Maeda, Midori; Kojima, Taisuke; Dishinger, John; Chantiwas, Rattikan; Takayama, Shuichi
Abstract : This work presents one-incubation one-hour multiplex ELISA enabled by aqueous two-phase systems for five-plex cytokine detection in human ThP-1 macrophages. Abstract : This work describes a convenient one-hour enzyme-linked immunosorbent assay (ELISA) formulated with conventional antibodies and horseradish peroxidase (HRP) reagents. The method utilizes aqueous two-phase system (ATPS) droplet formation based on poly(ethylene glycol) (PEG)-containing sample solution-triggered rehydration of dehydrated dextran (DEX) spots that contain all antibody reagents. Key advances in this paper include development of a formulation that allows a quick 1-hour overall incubation time and a procedure where inclusion of the HRP reagent in the PEG solution reduces the number of washing and incubation steps required to perform this assay. As an assay application, a 5-plex cytokine test compares cytokine secretion of differentially-treated human ThP-1 macrophages. Given the use of only readily available reagents and a common Western blot imaging system for the readout, this method is envisioned to be broadly applicable to a variety of multiplex immunoassays. To facilitate broader use, companion image processing software as an ImageJ plugin is also described and provided.